SAT0122 Experience of musculoskeletal ultrasound scanning improves skill of physical examination in assessment of synovitis. (12th June 2018) - Saku, A.; Furuta, S.; Furuya, H.; Suzuki, K.; Fukuta, M.; Makita, S.; Ito, T.; Ikeda, K.; Nakajima, H.
Abstract : Background: Assessment of presence/absence of joint swelling is one of the most essential factors in the management of rheumatoid arthritis (RA) patients. Although physical examination by touch is the basic assessment, it often varies among physicians. In contrast, it has been reported that musculoskeletal ultrasound (US) assessment is more objective and sensitive than physical examination in detecting synovitis. Objectives: We hypothesized accumulation of experience of physical examination by touch with checking results of simultaneous US assessment as right answers could improve the accuracy of physicians' physical examination by touch. This study aimed to compare the accuracy of physicians' physical examination by touch according to physicians' US experience when considering the results of US assessment as right answers. Methods: Seventy RA patients who planned to take US in daily clinical practice were enrolled. Twenty three physicians affiliated with Department of Allergy and Clinical Immunology at Chiba University Hospital were also participated in this study. Written informed consent was obtained from all the patients and physicians. At first plural physicians touched wrists, metacarpophalangeal (MCP) joints and proximal interphalangeal (PIP) joints and assessed swelling/non-swelling ("Ph swelling/non-swelling") of the joints. Subsequently, US assessment was performed by another physician blinded to the results of physical examination. In this study, "US swelling" and "US non-swelling" were defined as gray-scale imaging score (GS) ≳2 and GS ≲1. The positive predictive value (PPV) of physical examination by touch was calculated(="Ph swelling" joint count/"US swelling" joint count). Negative predictive value (NPV) was also calculated (="Ph non-swelling" joint count/"US non-swelling" joint count). The associated factors for PVV and NPV were identified by the univariate and multivariate logistic regression analysis. Results: The patients were median 65 years old with median 5 year history of RA. A majority of the patients was rheumatoid factor positive (59/70) and median DAS28-CRP was 2.63. A total of 6116 joints per physician were evaluated by touch, and the numbers of "Ph swelling" and "Ph non-swelling" joints were 990 and 5126. A total of 1540 joints were examined by US, the numbers of "US swelling" and "US non-swelling" joints were 172 and 1368. Overall PPV and NPV were 51.7% and 88.3%. Regarding PPV, multivariate analysis identified duration of physicians' attending to rheumatology clinic, wrists, tender joints, patients' gender, patients' age and Steinbrocker Stage as significant factors increasing the accuracy and patients' disease duration as a significant factor decreasing the accuracy. Regarding NPV, multivariate analysis identified duration of physicians' US experience and patients' disease duration as significant factors increasing the accuracy and wrists, tender joints, presence of osteophytes and DAS28-CRP as significant factors decreasing the accuracy. Conclusions: Experience of US improved accuracy of physicians' physical examination by touch in non-swelling joints and prevented overestimation, while experience of attending to rheumatology clinic rather than US improved the accuracy in swelling joints. Disclosure of Interest: None declared